Tackling antimicrobial resistance in the community. (30th September 2020) - Tonkie-Crine, S; Abel, L; Van Hecke, O; Wang, K; Butler, C
Abstract: Antibiotic prescription is a major driver of antibiotic resistance. The majority of antibiotic prescribing occurs in community care settings, often for respiratory infections. A substantial proportion of prescriptions are issued not according to guidelines, particularly for acute respiratory infections which can be self-limiting. Prescribers in these settings need support to prescribe antibiotics more prudently. Patients and the public also need support to manage infections which are self-limiting. This presentation presents a summary of how antimicrobial stewardship (AMS) activities are being used in community settings. Firstly, types of community-level interventions are discussed, including those aimed at clinicians, patients and the public. Next, we assess interventions based on their effectiveness at reducing antibiotic prescriptions or use and their cost-effectiveness. Finally, we discuss directions for future research and consider how the research to date could influence policy.